Exploring female Students’ perceptions of the influence of gender stereotypes on the choice of Mathematics at a Secondary School in Zimbabwe. - Musingarabwi, Starlin (Advances in Social Sciences Research Journal, 2020)
This study sought to explore the perceptions of female students of a secondary school regarding the infuence of gender stereotypes on their choice of mathematics and on prospects of pursuing it at tertiary level after they have successfully completed it at Advanced level. Involving a purposive sample of twenty students (11 Lower Sixth and 9 Upper Sixth) this qualitative case study employed slight quantitave data analysis. Questionnares, focus group discussions and Interviews were used to collect data. The study established that the majority of students were aware of common stereotypical conceptions that society ascribed to the learning of mathematics by girls. Gender had little impact on the decision to learn mathematics at Advanced and tertiary levels. Although some participants perceived mathematics as being more appropriate for boys than girls most participants indicated that the choice of mathematics at Advanced level and prospects of studying it at tertiary level were not so much about gender as they were about several factors. Recommendations for disabusing students’ stereotypical conceptions of the choice of mathematics choice are made from the findings of the study.